POST-KEYNESIAN INSTITUTIONALISM: CONTOURS AND FRONTIERS - Whalen, Charles (Brazilian Keynesian Review, 2023)
Post-Keynesian institutionalism (PKI)—a branch of the (original) institutionalist school that builds on common ground with post-Keynesianism—constitutes a robust tradition with secure foundations and broad methodological, analytical, and policy contours. Since its emergence in the 1980s, that tradition has consistently been ahead of the economic mainstream in shedding light on real-world problems. Drawing on the work of various heterodox economists—including John Kenneth Galbraith, Joan Robinson, Alfred Eichner, and Hyman Minsky—this article sketches the contours of today’s PKI, including its attention to institutional characteristics of labor and product markets, features of industrial organization, interrelations of finance and macroeconomics, and long-term trends in capitalist development. The article also discusses how PKI relates to the post-Keynesian economics of Fernando Cardim de Carvalho and surveys the frontiers of PKI. The discussion of frontiers and the article’s brief conclusion underscore post-Keynesian institutionalists’ commitment to an ever-evolving body of theory and policy research.